Improving Digital Accounting Information System Competence Through AkunBiz Application Training for MSMEs Rumah Kelor Anjani - Dwi Urip Wardoyo; Galuh Tresna Murti; Wiwin Aminah (PT. Berkah Digital Teknologi, 2025)
This community service program aims to enhance the digital accounting information system competencies of Micro, Small, and Medium Enterprises (MSMEs) through training on the AkunBiz Accounting application for Rumah Kelor Anjani MSMEs located in Cileunyi, Bandung Regency. The main problem faced by the partner is the continued use of manual financial recording, which hinders the preparation of accurate and timely financial reports. The implementation method included the delivery of basic accounting information system concepts, software demonstrations of the AkunBiz Accounting application, hands-on practice based on the partner’s business case studies, and evaluation using a Likert-scale questionnaire. The results indicate an improvement in participants’ understanding and practical skills in recording transactions and preparing digital financial reports. The final evaluation shows a satisfaction and effectiveness level of 95 percent, which falls into the very good category. The implementation of a locally developed digital accounting application is expected to improve the professionalism of financial management and support the sustainability and competitiveness of MSMEs in the context of an increasingly dynamic business environment. ABTRAK Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kompetensi sistem informasi akuntansi digital pelaku Usaha Mikro, Kecil, dan Menengah (UMKM) melalui pelatihan penggunaan aplikasi AkunBiz Accounting pada UMKM Rumah Kelor Anjani di Cileunyi, Kabupaten Bandung. Permasalahan utama yang dihadapi mitra adalah pengelolaan keuangan yang masih dilakukan secara manual, sehingga menyulitkan penyusunan laporan keuangan yang akurat dan tepat waktu. Metode pelaksanaan kegiatan meliputi pemberian materi konsep dasar sistem informasi akuntansi, demonstrasi penggunaan aplikasi AkunBiz Accounting, praktik langsung berbasis studi kasus usaha mitra, serta evaluasi menggunakan kuesioner skala Likert. Hasil kegiatan menunjukkan adanya peningkatan pemahaman dan keterampilan praktis peserta dalam melakukan pencatatan transaksi dan penyusunan laporan keuangan secara digital. Evaluasi akhir menunjukkan tingkat kepuasan dan efektivitas kegiatan sebesar 95 persen, yang termasuk dalam kategori sangat baik. Implementasi sistem informasi akuntansi digital melalui aplikasi lokal ini diharapkan mampu meningkatkan profesionalisme pengelolaan keuangan serta mendukung keberlanjutan dan daya saing UMKM di tengah dinamika bisnis modern.